Cantar em português: um estudo sobre a abordagem articulatória como recurso para a prática do canto - Mattos, Wladimir Farto Contesini de [UNESP] (2014)
This paper deals with the phonetic-articulatory processes of the singing voice due to the juxtaposition of the verbal syllable and the musical note, considered here to be the smallest components of the melodic line. In our hypothesis, good articulation of the melodic line depends on the control of the articulatory processes involved in the internal and external forms of the syllables, coupled with the articulatory processes which define the phases of the dynamic envelope of the notes. As a reference for the treatment of these articulatory processes, in the context of studies of diction applied to singing, we propose the theoretical representation of the ‘melodic syllable’. This model has as its base the structure of the verbal syllable made up of three subcomponents (attack, nucleus, coda), coupled with the model of the dynamic envelope of the musical note in three parts (attack, sustain, release). In the context of this work, we refer to ‘articulatory treatment’ of the use of the ‘melodic syllable’ as a resource for the pedagogic practice of song interpretation. This proposal was developed specifically using the articulatory characteristics of Brazilian Portuguese, in order to give the native speaker of this language a reference in relation to sung BP for the sung pronunciation of other languages